Production processes of renewable aviation fuel : present technologies and future trends /: present technologies and future trends. (2021) - Gutiérrez-Antonio, Claudia; Romero-Izquierdo, Araceli Guadalupe; Gómez-Castro, Fernando Israel; Hernández, Salvador
No abstract available